Mycobacterium abscessus pulmonary disease presenting with spontaneous pneumomediastinum and subcutaneous emphysema in childhood acute lymphoblastic leukemia: a case report and literature review - Wenyuan Liu; Jinhua Chu; Zhiwei Xie; Linhai Yang; Lingling Huang; Songji Tu; Huaju Cai; Zhengyu Wu; Anbang Wei; Chengzhu Liu; Yan Cheng; Kunlong Zhang; et al. (BMC, 2023)
Abstract Introduction Mycobacterium abscessus is a rapidly growing mycobacterium commonly identified in adults with underlying pulmonary diseases but is rarely observed in children. A better understanding of this pathogen in children is essential. Case presentation We report the case of a 49-month-old female child without previous underlying pulmonary diseases but with acute lymphoblastic leukemia (ALL). The patient was complicated with pneumonia during chemotherapy, which was primarily characterized by spontaneous pneumomediastinum and subcutaneous emphysema on chest computed tomography (CT). M. abscessus sequences were detected by metagenomic next-generation sequencing in bronchoalveolar lavage fluid. With mechanical ventilation, closed thoracic drainage, and anti-infective therapy for 6 months, the patient's infection was controlled. The patient completed 2.5 years of treatment for ALL, and the drugs were discontinued. The patient currently remains in complete hematologic remission. Discussion We reviewed the literature on 33 children with M. abscessus pulmonary disease. These children mostly had underlying immunodeficiency. Chest CT most often showed nodular shadows, consolidation, and bronchiectasis. Spontaneous pneumomediastinum and subcutaneous emphysema were not reported as major manifestations. Conclusion Spontaneous pneumomediastinum and subcutaneous emphysema were our patient's main characteristics on chest CT, and this study enriches the knowledge regarding possible imaging changes in M. abscessus pulmonary disease in children. This case report reflects good clinical experience in maintaining the balance between chemotherapy and anti-infective therapy in childhood ALL.